Reminders of Mortality Alter Pain-Evoked Potentials in a Chinese Sample - Wang, Chenbo; Tian, Jing (Frontiers in Psychology, 2018)
Pain is of evolutionary importance to human survival. However, the perception of pain could be changed when death-related thoughts are accessible. Although the influence of mortality salience (MS) on pain processing has been investigated in Westerners recently, it is unclear whether this effect is constrained by specific culture context since humans may employ cultural worldviews to defend the existence problem. The current study tested whether and how MS affected pain processing in a Chinese male sample. We primed participants with sentences indicating MS or negative affect (NA) on either of two days. Both before and after the priming, event-related potentials (ERPs) elicited by painful and non-painful electrical stimulations were recorded. Results showed that pain-evoked potentials were identified as an early negative complex N60-P90-N130 and a late positivity P260. Pain-evoked N130 after MS priming was larger than that after NA priming. Meanwhile, pain-evoked P260 decreased after MS priming but not after NA priming. These findings indicate that reminders of mortality affect both early sensory and late cognitive neural responses related to physical pain. Although previous studies reporting an increased effect of MS on perceived pain intensity in Westerners, we found an unchanged or possibly reduced effect in Chinese. Thus, the current work provides insight into a culture-sensitive perspective on how pain processing would be modulated when existential problem occurs.